Effect of Coupling Agent on Softwood Kraft Nanocellulose Fibril-Reinforced Polylactic Acid Biocomposite. (24th December 2021) - Saeed, Usman; Rathur, Sami Ullah; AlTuraif, Hamad; Bamufleh, Hisham
Abstract : The nanocellulose fibril produced by using natural sources can be used in developing sustainable and green products. The useful features of nanocellulose fibril can include valuable physical properties, appropriate surface chemistry, low toxicity, and biocompatibility. The study presented shows the use of polylactic acid with five different percentages of nanocellulose fibril and the use of 3% maleic anhydride as a coupling agent. The maleic anhydride acts as coupling agent which improves the thermochemical and thermomechanical characteristics of the end product. The addition of 3% maleic anhydride as coupling agent with 10% nanocellulose fibril improved the impact strength up to 14.3%, elastic modulus up to 40.6%, and tensile strength up to 30.1%. Furthermore, the dynamic mechanical analysis result indicates that the inclusion of maleic anhydride improved the toughness by reducing the tan δ peak and increases the storage modulus. Finally, the scanning electron micrograph shows that the interfacial compatibility between nanocellulose fibril and polylactic acid matrix is improved with the addition of maleic anhydride.